Pencegahan Virus Covid-19 melalui Pelatihan dan Pendampingan Edukasi Bagi Masyarakat Terdampak - Eli Mufidah (TAAWUN, 2021)
The lack of understanding in education field of the people at Peluk, Pandowolimo Village, Karangbinangun, Lamongan, finally has the impact on the lack of knowledge that correlated on the importance healthy care and implementing the healthy lifestyle during the pandemic. This can be seen from the behavior of people who ignore health protocols. This Dedication Focuses on mentoring efforts and educational training about the importance of preventing covid-19, which aims to provide understanding to the public about COVID-19 prevention, and aims to provide training to make personal protective equipment such as masks and hand sanitizers. Therefore, this assistance uses three stages, namely planning, implementation, and results. The planning stage is conducting an observation, compiling a schedule, and making a Forum Group Discussion (FGD). The implementation stage was carried out, namely COVID-19 prevention education which was disseminated to the public and to students in formal and non-formal institutions, either through direct or indirect education. Furthermore, the community was also given training in making masks and hand sanitizers. The last stage is distributing masks and hand sanitizers to people in need. The result is the formation of a good public understanding of COVID-19 and its prevention, besides that the public can also make personal protective equipment such as masks and hand sanitizers.